A commutation analytical model for quench protection of the CFETR central solenoid model coil. (14th April 2020) - DENG 邓, Tianbai 天白; GAO 高, Ge 格; WU 吴, Yanan 亚楠; LI 李, Jun 俊; FU 傅, Peng 鹏; LIU 刘, Sheng 生; WANG 王, Min 敏
Abstract: A central solenoid model coil will be set up to develop and verify the technique for the full-size central solenoid coil of the China Fusion Engineering Test Reactor. In case of quench and failures of superconducting coils, the quench protection (QP) system, which employs fuse-based commutation technology, is designed. This paper presents an analytical model to investigate the commutation process in the QP circuit. The model consists of the QP circuit equations, the breaker arc model, the fuse pre-arc model, and the fuse arc model. The model is employed in the whole commutation process including current transfer from breaker branch to the fuse branch model, then from fuse branch to the discharge resistor branch, and current decrease to zero in the discharge resistor. The experiment result verified the effectiveness of the presented model. The model might be helpful for design of the fuse and optimization of the commutation circuit.